Implementation of community-driven initiative program in strengthening discipline character in elementary school - Zulfasari, Putri Sulistia; Sukma, Hanum Hanifa (Jurnal Ilmiah Pendidikan Dasar, 2025)
Discipline is a fundamental aspect in shaping students character within the school environment. However, in reality, various forms of student non-compliance with school regulations are still found, such as tardiness, lack of involvement in the daily class picket schedule, and insufficient awareness of maintaining cleanliness. This issue occurs at Kramatwatu 2 Elementary School and requires strategic efforts for its resolution. This study aims to analyze the implementation of the community-driven initiative program in strengthening students discipline character as a strategy to foster student discipline and responsibility. This research employs a qualitative approach with a case study design. The  research subjects consist of third-grade teachers and students. Data collection techniques include observation, in-depth interviews, and source triangulation to ensure data validity. Data analysis is conducted using the Miles and Huberman model, which involves stages of data reduction, data presentation, and conclusion drawing. The research findings indicate that teachers apply various strategies in this program, such as the formation of student groups with  positive character identities,  the use of emotional bag media as a means of self-reflection, and the implementation of a daily picket system in class. Furthermore, efforts to understand individual student characteristics are carried out through observation and direct interaction. This study also identifies supporting factors and obstacles in the program's implementation, which need to be addressed to ensure the program's sustainability and effectiveness in shaping students discipline character.